Work together, move together—Cooperation and rapport promote interpersonal synchrony - Clara Scheer; Daniel L. Bowling; Niklas A. Hungerländer; W. Tecumseh Fitch; Lisa Horn (PLoS ONE, 2025)
Human movement synchrony is one fundamental driving force for social bonding and yet not all individuals are equally likely to engage in interpersonal synchrony. Movement synchrony increases collaboration and feelings of rapport, but it remains unclear whether cooperative interactions between two individuals also result in greater interpersonal synchrony. The aim of the current study was to investigate whether cooperating in one task increased spontaneous movement synchrony in a subsequent unrelated task. Thirty-four same-gender dyads first worked on a jigsaw puzzle – either collaboratively or individually – and subsequently jumped on trampolines facing each other. Additionally, we investigated the potential effects of the participants’ rapport and mood during the experiment. As predicted, dyads who had worked on the puzzle collaboratively displayed greater movement synchrony when later jumping on trampolines than dyads who had worked individually. When we tested for the additional influence of the participants’ initial rapport and mood, however, the effect of the collaborative treatment was qualified by a stronger effect of initial rapport. The results of the current study provide evidence that collaborative interactions and initial rapport are important stepping stones towards interpersonal synchrony and add to the growing body of evidence suggesting that human cooperation and interpersonal synchrony are essentially connected.